Visiting Index: Supporting decision-making on Open Urban Spaces - CHONDROGIANNI, Dimitra; STEPHANEDES, Yorgos (European Journal of Geography, 2022)
This Open urban space functions as the stage of the city where public life unfolds. These spaces, which provide traffic networks, communication nodes and common spaces for play and relaxation and play a key factor in shaping cities and enhancing urban resilience. Forming and planning urban spaces is a complex and demanding process and, in many cases, the final approved proposal lies upon city decision-makers. Supporting stakeholders to approve plans and regeneration actions creating desirable open spaces, corresponding to urban living needs, seems crucial. In this framework, the research focuses on identifying the priorities of the decision-making prosses and citizens’ preferences on open urban spaces. In addition, the way in which citizens’ preferences define the number of their visits to an urban space is investigated in order to develop a model estimating Demand side on open urban spaces. As the parameter of Supply of open urban areas should not be ignored in this process, the Visiting Index is developed as the key performance indicator to be under study by stakeholders. At last, considering that urban areas are complex, dynamic systems evolving rapidly, the dynamic relationships among the parameters of Visiting Index are described in Casula Loop Diagram to contribute to making open urban spaces effectively manageable.